Investigating gait behavior in children with scoliosis diagnosed Juvenile Idiopathic Arthritis: Pilot Study - Leblebici, Gökçe; Kısa, Eylül Pınar; Tarakcı, Ela; Kasapçopur, Özgür (Gait & posture, 2023)
Juvenile Idiopathic Arthritis (JIA) is one of the common chronic diseases in childhood and can be identified by chronic joint swelling, limitations, and painful range of motion (1). Even in unaffected joints, arthritis may change the loading and the kinetic chain is modified by this (2). All these situations may lead to scoliosis in these children. However, the affecting variables of gait behavior in children with scoliosis diagnosed with JIA are still unknown due to a lack of evidence in the literature. What is the gait behavior in children with scoliosis diagnosed with Juvenile Idiopathic Arthritis? 8 children (11,73±2,65 years) with adolescent idiopathic scoliosis (AIS) diagnosed with JIA and 7 healthy age-matched children were included in the study. Center of force mass (CoM) displacement, stance time durations (initial contact, loading response, midstance, terminal stance and stance phase duration), foot angle and foot loading in 6 different sole areas during gait were obtained using the FreeMed baropodometry platform (the FreeStep v. 1.0. 3 88 software, Sensor Medica, Guidonia Montecelio, Roma, Italy). Independent Sample T-test was conducted to compare the interested parameters between groups. There were no significant differences in stance phase and subphase durations between groups (p>0.05). However, on the dominant side, the loading percent at hallux was lower in patients than controls, and on the non-dominant side, loading percent at hallux and 4th -5th metatarsal were lower in patients than controls during gait (Table) (p<0.05). [Display omitted] The pilot results of the present study show that loading patterns in children with scoliosis diagnosed with JIA differ from healthy controls. According to Bruyneel et al. (3), the AIS had an asymmetric bilateral loading pattern and increased loading at the medial or lateral plantar area depending on the scoliosis's direction. Children with AIS diagnosed with JIA has less loading at the hallux area, which may affect the first ray and push-off during gait (4). With extended results of the study, the gait behavior of the children with AIS diagnosed with JIA will be understood clearly.